Incidence of cardiac arrhythmias and left ventricular hypertrophy in recreational scuba divers - Buzzacott, Peter; Anderson, George; Tillmans, Frauke; Grier, James; Denoble, P.J. (South Pacific Underwater Medicine Society, 2021)
Introduction: The aims of this study were to investigate the potential impact of age, sex and body mass index (BMI) upon the incidence of arrhythmias pre- and post- diving, and to identify the prevalence of left ventricular hypertrophy (LVH) in older recreational divers.